2018
DOI: 10.24170/15-3-3182
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective audit of mitral valve repair surgery at Tygerberg Hospital

Abstract: Background: Mitral valve repair is well established as the preferred treatment modality for the majority of patients with degenerative mitral valve disease requiring intervention. Valve repair offers a distinct event-free survival advantage compared with replacement with either a bioprosthetic or mechanical valve. At present, there are little data available on the management and outcome of mitral valve repair in South Africa. The aim of this study is to describe and compare the indications, specifi c pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…Published data approximate the peri-operative mortality rate of mitral valve surgery to be 3%, dependent on the population and the peri-operative risk of the patient prior to surgery. (3,28) In contrast to internationally published data, our peri-operative mortality rate was 6.1%. RHD is the main form of valve heart disease in Africa.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Published data approximate the peri-operative mortality rate of mitral valve surgery to be 3%, dependent on the population and the peri-operative risk of the patient prior to surgery. (3,28) In contrast to internationally published data, our peri-operative mortality rate was 6.1%. RHD is the main form of valve heart disease in Africa.…”
Section: Discussioncontrasting
confidence: 89%
“…(1,2) Studies from Africa confirm that RHD is the main cause of cardiac morbidity and mortality from heart surgery. (1)(2)(3) Mitral valve disease, in the form of mitral stenosis and mitral regurgitation, is the commonest form of valve disease and its treatment usually involves surgical repair or replacement. These surgical procedures are highly invasive and not without risk of complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional repair for patients with IE are in the minority as most patients have extensive valvular destruction due to IE with underlying rheumatic valve involvement. In a recent 5-year retrospective audit of mitral valve repair at Tygerberg Hospital (Cape Town, South Africa), only a small number of patients with IE had successful mitral valve repair (28). A new emerging alternative for patients not suitable to conventional repair is reconstruction of the anterior mitral valve leaflet (AMVL) with autologous venous tissue (29,30).…”
Section: Surgical Therapymentioning
confidence: 99%
“…Reinfection rates are very low with conventional repairs and it is reasonable to predict that reinfection rates should be lower with this approach compared to mechanical valve replacement (31). A recent review of mitral valve repairs at Tygerberg Hospital (Cape Town, South Africa) reported no patients with relapse/reinfection in patients with IE that underwent mitral valve repair within 6 months of surgery (28).…”
Section: Surgical Therapymentioning
confidence: 99%